Impacts of New Entry and Horizontal Joint Ventures on Industrial Rates of Return - Duncan, Jerome L. (The Review of Economics and Statistics, 1982)
Data Resources, Inc., Regional Load-Curve Models, vols. 1 and 3 (Aug., Sept. 1981). Engle, Robert, Clive W. J. Granger, Allen Mitchem, and Ramu Ramanathan, Some Problems in the Estimation of Daily Load Shapes and Peaks, Modelling and Analysis ofElectricity Demand by Time-of-Day, Electric Power Research Institute (EPRI), EA-1304, Dec. 1979. Engle, Robert F., Clive W. J. Granger, and Ramu Ramanathan, Regional Load Curs e Models: QUERJ's Model Long Run Forecasts and Sensitidvity Analysis, EPRI, EA-1672, vol. 4 (Sept. 1981). Granger, Clive W. J., Robert F. Engle, Ramu Ramanathan, and Allan Andersen, Residential Load Curves and Time-of-Day Pricing: An Econometric Analysis,' Journal ofEconometrics 9 (1979), 13-32. Granger, Clive W. J., et al., A Regional Load Curve Model: Specification and Estimation, Electric Power Research Institute, forthcoming. Graybill, Franklin, Theory and Application of the Linear Model (North Scituate, MA: Duxbury Press, 1976). Hanushek, Eric A., Efficient Estimators for Regressing Regression Coefficients, The American Statistician 28 (May 1974), 66-67. Mitchem, Allen, A Regional Model of Time of Day Elasticity Demand: A Tiuo Stage Approach, unpublished PhD dissertation, University of California at San Diego, 1981. Poirier, Dale, Economic Issues in Land Forecasting, Modelling and Analysis of Electricity Demand by Time-oJ-Day, EPRI, EA-1304, Dec. 1979. Ramanathan, Ramu, Robert F. Engle, and Clive W. J. Granger, Regional Load Curlve Models: QUERJ's Model Long Run Forecasts and Sensitivity Analysis, EPRI, EA-1672, vol. 2 (Aug. 1981). University of Arizona Engineering Experiment Station, Modelling and Analysis of Electricity Demand by Time-of-Day, EPRI, EA-1304, Dec. 1979 (proceedings of the EPRI workshop at San Diego). U.S. Department of Commerce, Notes on TemperatureHumidity Index, L.S. 5922, June 1959.